Analysis Of the Effect of Brand Image, Packaging, And Digital Marketing on Purchase Decision - I Kadek Jati Negara; Ni Made Wulandari Kusumadewi (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to analyze the effect of brand image, packaging, and digital marketing on consumer purchasing decisions for the Loloh Cem-cem Ibu Kunil product in Penglipuran Tourism Village, Bangli Regency. The background of this research is based on the phenomenon of increasing competition among MSMEs and the importance of effective marketing strategies to enhance purchasing decisions. This study employs a quantitative approach with an associative research type. The research population consists of consumers of Loloh Cem-cem Ibu Kunil, with a total sample of 160 respondents obtained through purposive sampling techniques. Data were collected using questionnaires, while data analysis was conducted through multiple linear regression. The results show that brand image, packaging, and digital marketing have a positive and significant effect on purchasing decisions. Partially, brand image has the most dominant effect compared to the other variables, followed by packaging and digital marketing. Simultaneously, the three independent variables explain the variation in purchasing decisions with a coefficient of determination (R²) value of 34.2 percent. These findings emphasize the importance of strengthening brand image, optimizing packaging design, and utilizing digital marketing strategies to enhance consumer purchasing decisions, particularly for local traditional beverage products.